Uterine myometrial mature teratoma presenting as a uterine mass: a review of literature. Issue 1 (December 2016) - Kamgobe, Emmanuel; Massinde, Anthony; Matovelo, Dismas; Ndaboine, Edgar; Rambau, Peter; Chaula, Tito
Abstract Background Teratomas are a germ cell tumors composed of two or more tissues which originate from ectoderm, endoderm or mesoderm. These tumors commonly arise from the ovary although other extragonadal sites can be involved, especially in children. Case presentation We report a case of a 21-year-old female of Sukuma ethnicity from the northern region of Tanzania who presented with abdominal pain and distension, fever, and abnormal vaginal discharge for the previous three weeks. The patient was also lactating for the previous 8 months following cesarean section delivery. Pelvic ultrasound suggested pelvic abscess but after laparotomy and histological analysis of a bulky uterus removed a diagnosis of mature uterine teratoma was confirmed. Conclusion Although it is rare, uterine teratoma should be considered in differential diagnosis to any patient with uterine mass even without typical radiological findings.